Analysis of Environmental Literacy of Puspita High School Students, Air Kumbang District, Banyuasin Regency - Siti Nurhayati; Wulandari Saputri (Universitas Wiralodra, 2024)
This study aims to analyze the environmental literacy of students at Puspita High School, Air Kumbang District, and Banyuasin Regency related to biotic and abiotic components in oil palm plantations. This study uses a quantitative descriptive approach with a data collection method through an environmental literacy questionnaire. The population of this study is 175 students of class X phase E, and the research sample of class X1 is 35 students. The results showed that most of the population had environmental literacy skills at a